1990
DOI: 10.1111/j.1464-5491.1990.tb01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Cardiovascular Risk Factors in Type 2 Diabetes Mellitus

Abstract: Prospective studies have shown that increased urinary albumin excretion is a risk factor for cardiovascular morbidity and mortality in patients with Type 2 diabetes mellitus, but the nature of the association remains unknown. Eighty-five patients aged less than 65 years and not treated with insulin were studied. The overnight albumin excretion rate (AER) was measured in each patient and analysed in relation to several putative risk factors for cardiovascular disease. AER was used both as a continuous variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 18 publications
5
10
0
Order By: Relevance
“…The association of abnormal UAE with higher prevalence of coronary heart disease, stroke and lower-extremity amputation is consistent with other reports [4,5,27,36]. The expected associations between increased UAE and diabetic retinopathy was present in all centres and consistent with previous observations [4,22,26].…”
Section: Discussionsupporting
confidence: 82%
“…The association of abnormal UAE with higher prevalence of coronary heart disease, stroke and lower-extremity amputation is consistent with other reports [4,5,27,36]. The expected associations between increased UAE and diabetic retinopathy was present in all centres and consistent with previous observations [4,22,26].…”
Section: Discussionsupporting
confidence: 82%
“…More recently, these findings have been confirmed in two prospective studies (10,11) in which, besides diabetes duration, age, and glycemic levels (3,8,9), other major atherosclerotic risk factors, such as smoking, body weight, high blood pressure (BP) (12)(13)(14), and lipid and lipoprotein abnormalities (15,16) frequently associated with microalbuminuria, were taken into account.…”
mentioning
confidence: 68%
“…Increased cardiovascular risk in type II diabetic patients with microalbuminuria cannot be merely attributed to coexisting risk factors, such as higher BP (7), obesity (7), unfavorable lipid profile and lipoprotein composition (12)(13)(14)(15), elevation in serum lipoprotein(a) concentrations (16), smoking (10), poorer glucose control (7), and disorders of the hemostatic system (44). Thus, other mechanisms must be examined to explain the higher susceptibility of type II diabetic patients with microalbuminuria toward macrovascular disease (45).…”
Section: Conclusion-mentioning
confidence: 99%
“…For example, the prevalence of microalbuminuria has been reported as 7±10% and 2±3%, in diabetic and non-diabetic European people, respectively. 18 By comparison, Allawi et al 5 reported microalbuminuria in 26% of Asian Indian people with NIDDM, Collins et al 6 reported prevalences of 26% in men and 30% in women from the Paci®c Island of Nauru, Haffner et al 8 reported a prevalence of microalbuminuria of 13% in non-diabetic Mexican Americans, Robbins et al 19 reported prevalences in American Indians of 28.3% in Arizona, 15.1% in Oklahoma and 13.8% in North and South Dakota, and we have reported prevalences of microalbuminuria in European, Maori, Paci®c Island and Asian New Zealanders of 2.7%, 15.6%, 13.0% and 8.0%, respectively. 15 There is no simple explanation for the ethnic differences in prevalences of microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%